Development of green design framework for Malaysian automotive industries - K., Li Wei; Mat Saman, Muhamad Zameri; L., Meng Chiao (2008)
Currently the level of competition is intensifying as the business environment shifts from being national to global. As manufactured vehicles have become more global, the competitive pressures from multi-national companies have increased substantially. Based on that, it is clearly shows that, the important of understanding the implementation of green indicators concept. This situation will be giving a big impact to the Malaysian automotive industries to become more competitive in the world market. Furthermore, with realization of Asian Free Trade Area (AFTA) in 2005, it has badly hit Malaysian’s carmaker sales. Malaysia used to be the largest automotive market in Asian but recently it has been overtaken by Thailand and Indonesia. Prior to AFTA, the Malaysian automotive industries enjoyed considerable growth but now faces intense competition from Asian and other global manufacturers. Based on that, there is a strong need for this concept in designing a vehicle. It could provide assistance in making decisions at the early stage of the vehicle design and development process in order to avoid the costs and time consumed through later redesign. It is believed that this project is becoming a key factor in order to help National Automotive Policy (NAP) to achieve their objective and make it reality and also the proposed output in this research can help Malaysian car manufacturers to become more competitive. Hence, the aim of this paper is to highlight the establishment of Green Design framework for Malaysian automotive industries by establishing a set of ‘Critical Success Factors’ and ‘Critical Parameter Chain’ that will be applied at the design stage. As a summary, this paper will highlight the new paradigm in product design and development process by using green design concept